Will coral reefs survive by adaptive bleaching?. Issue 1 (14th March 2022) - Cunning, Ross
Abstract : Some reef-building corals form symbioses with multiple algal partners that differ in ecologically important traits like heat tolerance. Coral bleaching and recovery can drive symbiont community turnover toward more heat-tolerant partners, and this 'adaptive bleaching' response can increase future bleaching thresholds by 1–2°C, aiding survival in warming oceans. However, this mechanism of rapid acclimatization only occurs in corals that are compatible with multiple symbionts, and only when the disturbance regime and competitive dynamics among symbionts are sufficient to bring about community turnover. The full scope of coral taxa and ecological scenarios in which symbiont shuffling occurs remains poorly understood, though its prevalence is likely to increase as warming oceans boost the competitive advantage of heat-tolerant symbionts, increase the frequency of bleaching events, and strengthen metacommunity feedbacks. Still, the constraints, limitations, and potential tradeoffs of symbiont shuffling suggest it will not save coral reef ecosystems; however, it may significantly improve the survival trajectories of some, or perhaps many, coral species. Interventions to manipulate coral symbionts and symbiont communities may expand the scope of their adaptive potential, which may boost coral survival until climate change is addressed.